2022
DOI: 10.3390/jpm12071039
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Photodynamic Therapy Using Indocyanine Green Liposomes for Refractory Cancer

Abstract: We reported the development of an effective cancer treatment using a multidisciplinary treatment, including photodynamic therapy (PDT) with indocyanine green (ICG) liposomes and a combination of Lentinula edodes mycelia (LEM) and hydrogen gas inhalation therapy. ICG liposomes were prepared by adding 5 mg of ICG to 50 mL liposomes. Later, 25 mL of ICG liposomes were diluted with 250 mL of 5% glucose solution and administered intravenously to the patient. We selected the multi-laser delivery system (MLDS), a las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
11
1
1
Order By: Relevance
“…In addition, CDDP liposome intervention demonstrated some antitumor efficacy in both participants in the present study. The effect of sodium thiosulfate cannot be ruled out in terms of the side effects caused by CDDP in the present study [25]; however, we believe that the present results are due to the liposomalization of CDDP, as shown in Figure 4, and previous studies that used similar liposomes have also reported liposome-related EPR effects [17]. Furthermore, previous reports of CDDP liposomes reducing cytotoxicity in humans in clinical trials and in vitro studies support the present study's results [26][27].…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…In addition, CDDP liposome intervention demonstrated some antitumor efficacy in both participants in the present study. The effect of sodium thiosulfate cannot be ruled out in terms of the side effects caused by CDDP in the present study [25]; however, we believe that the present results are due to the liposomalization of CDDP, as shown in Figure 4, and previous studies that used similar liposomes have also reported liposome-related EPR effects [17]. Furthermore, previous reports of CDDP liposomes reducing cytotoxicity in humans in clinical trials and in vitro studies support the present study's results [26][27].…”
Section: Discussioncontrasting
confidence: 48%
“…1,2-Dimyristoyl-sn-glycero-3-phosphocholine (DMPC) was purchased from Yuka-Sangyo Co., Ltd. (Tokyo, Japan), and CDDP was purchased from Nichi-Iko (Sogawa, Japan). Liposomes were prepared as previously reported (17). Briefly, DMPC was dissolved in a 5% glucose solution at a concentration of 8.85 mM using a Bransonic ® CPX8800H-J Ultrasonic Cleaner (Branson Ultrasonic Co., Ltd., Danbury, CT, USA) and then sonicated at 40 kHz for 60 min under 45 °C.…”
Section: Preparation Of Cddp Liposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…More preclinical and clinical studies suggested that ICG-based photoresponsive liposomes may be an alternative to chemotherapy. As a piece of evidence, Yorozu and colleagues reported a classic case of ICG photoresponsive liposomes used in the treatment of human advanced cancer. ICG photoresponsive liposomes were injected intravenously into the cancer tissues of patients with middle intrathoracic esophagus carcinoma.…”
Section: Photoresponsive Liposomes Based On Organic Photosensitizersmentioning
confidence: 99%
“… 5 However, major drawbacks were reported in different clinical trials in relation to porphyrin-related PSs, such as slow excretion, high bioaccumulation and strong adverse reactions to visible light. 6 A particularly interesting PS is Indocyanine Green (ICG). ICG is an FDA approved fluorescent dye that is currently used in oncology to track sentinel lymph nodes in breast cancers (BCs) and is widely adopted in laparoscopic surgery to enhance visibility and provide detailed anatomical information during surgery.…”
Section: Introductionmentioning
confidence: 99%